2010
DOI: 10.22358/jafs/66278/2010
|View full text |Cite
|
Sign up to set email alerts
|

The role of animal feeding trials for the nutritional and safety assessment of feeds from genetically modified plants – Present stage and future challenges

Abstract: The world´s population is still growing up and asking for more and better food. High yielding plants with low external inputs should be the main aim of plant breeding to meet the higher demand for man and animal. Apart from traditional breeding plant biotechnology seems to have a certain potential to contribute to this objective. Safety and nutritional studies with such modified plants are the most important prerequisites for public acceptance of derived feed and food.The first step for safety and nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A critical review of the other published studies where change(s) in some parameters are reported to result from GE feed also reveal deviations from standard protocols [ 14 , 15 , 79 ]. These include control feed that was not derived from near isogenic lines, insufficient animal numbers for statistical power, over interpretation of differences which lie within the normal range of variation and hence are not biologically significant, and/or poor toxicological interpretation of the data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A critical review of the other published studies where change(s) in some parameters are reported to result from GE feed also reveal deviations from standard protocols [ 14 , 15 , 79 ]. These include control feed that was not derived from near isogenic lines, insufficient animal numbers for statistical power, over interpretation of differences which lie within the normal range of variation and hence are not biologically significant, and/or poor toxicological interpretation of the data.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific question being addressed by feeding studies should be well-established before designing the study [ 79 ]. Designing experiments to test for intended effects is relatively straightforward.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant breeding can be considered as the starting point of the food chain all over the world [3][4][5][6][7][8], as shown in the simple food chain model in Figure 1. Traditional breeding, as well as "green" biotechnology or green chemistry [9], may result in changing of composition and nutritive value of feed plants.…”
Section: Introductionmentioning
confidence: 99%